Creation, Transformation and Metamorphosis - Mário S. Ming Kong; Maria do Rosário Monteiro; Maria João Pereira Neto (CRC Press, 2025)
The texts presented in Proportion Harmonies and Identities (PHI) - Creation, Transformation and Metamorphosis were compiled to establish a multidisciplinary platform for presenting, interacting, and disseminating research. It also aims to foster awareness and discussion on Creation, Transformation and Metamorphosis, focusing on different visions relevant to Architecture, Arts and Humanities, Design and Social Sciences, and its importance and benefits for the sense of identity, both individual and communal. Creation, Transformation and Metamorphosis has been a powerful motor for development since the Western Early Modern Age. Its theoretical and practical foundations have become the working tools of scientists, philosophers, and artists, seeking strategies and policies to accelerate development in different contexts.The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives 4.0 license.